The Relationship between Sodium Intake, Stress Levels, and Physical Activity on Prehypertension among Adolescents - Riska Damayanti; Widya Astuti; Hurry Mega Insani; Ahdiyatul Fauza (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Prehypertension is posing a significant health concern as it has the potential to develop into full hypertension if not addressed. The city of Bandung is noted for having one of the highest hypertension prevalence rates in West Java, reaching 23.5%. Among adolescents, prehypertension may arise from poor lifestyle habits, such as imbalance dietary intake, excessive nutritional status, insufficient physical activity, genetic factors, and socioeconomic factors. The study aimed to examine the relationship between sodium intake, physical activity, and stress levels with prehypertension among adolescents at SMAN 17 Bandung. Employing a quantitative cross-sectional design, the research was conducted from October 2024 to April 2025 at SMAN 17 Bandung. A total of 60 respondents were selected using purposive sampling. Sodium intake was assessed through two 24-hour dietary recalls. The PAL (Physical Activity Level) questionnaire was used to evaluate physical activity, while the Depression Anxiety Stress Scales (DASS) questionnaire measured stress levels. The Chi-Square was used for bivariate data analysis. Findings revealed that 53.7% of the adolescent participants experienced prehypertension. Statistical analysis demonstrated significant correlations (p<0.05) between sodium intake (p=0.000), physical activity (p=0.042), and stress levels (p=0.007) with prehypertension among adolescents at SMAN 17 Bandung. There is an effect of sodium intake, physical activity, and stress levels with prehypertension among adolescents at SMAN 17 Bandung